Chinese Visceral Adiposity Index and Depressive Symptoms in Middle-Aged and Elderly Chinese: Dose-Response Correlation and the Effect Mediated by Sleep Time and Life Satisfaction - Wang, Miyuan; Pan, Liang; Peng, Hongye; Song, Bin; Zeng, Yan; Qian, Mingtao; Yang, Qing; Xie, Shanshan; Mai, Gang; Wang, Hui (Depression and Anxiety, 2023)
Depression is a common psychosomatic disorder in clinical practice and may soon become the largest disease burden globally. Studies have focused on the association between obesity and depression but presented controversial results. This study is aimed at exploring the dose-response correlation between Chinese visceral adiposity index (CVAI) and depressive symptoms and the mediating effect of sleep time and life satisfaction in this relationship. We include 4149 individuals aged ≥45 years from wave 2011 and wave 2015 of China Health and Retirement Longitudinal Study (CHARLS), using restricted cubic spline (RCS) to examine possible nonlinear correlation and serial multiple mediation model to examine the mediating effect of sleep time and life satisfaction. Results indicate that there is a significant negative linear correlation between CVAI and depressive symptoms, and each IQR increment in CVAI is associated with 11% lower risk of depressive symptoms. About 50.00% (indirect effect/total effect) of the significant association between CVAI and depressive symptoms is mediated by sleep time and life satisfaction, with life satisfaction playing a relatively major role. Properly visceral adiposity may be protective against depressive symptoms. It could be feasible to alleviate the depressive symptoms in people with too low visceral adiposity by improving their life satisfaction.